Beliefs Assessment of the Faculty of Sport Sciences Students in Nutritional Supplements and Health Literacy - Ustundag Ocal, Nursel; Onen, Cihan; Cihan, Bekir Baris (Progress in Nutrition, 2022)
Study Objectives: This study aimed to assess the relationship between the level of belief in nutritional supplements and the health literacy of students studying at the Faculty of Sport Sciences. Methods: This descriptive and correlational study was conducted with the students of the Faculty of Sport Sciences of a state university in the Central Anatolia Region of Turkey. This study was completed with 804 students who agreed to participate. The data were collected using the socio-demographic data form (16 questions), the Turkish Health Literacy Scale-32 (THLS32), and The Scale of Beliefs of Sports Supplements Turkish Version prepared by the researchers. Results: A significant difference was found between the department where university students studied, where they stayed, and the belief in sports nutritional supplements. Meanwhile, in the health literacy index, a significant difference was found only with the chronic disease status. 47.4% of the students took energy drinks and 47% took dietary supplements. The health literacy of 68.8% of the participants was at an adequate/excellent level. No significant correlation was found between THLS32 and the belief in sports nutrition supplements. Conclusion: It has been determined that students of the faculty of sports sciences widely used dietary supplements and observed that the belief in dietary supplements did not change significantly with the increase of health literacy. Having a high nutritional supplement belief score might increase the use of banned supplement products, such as doping among students. Health education on nutritional supplements should be given to students, including trainers.